Narrative Structure in Ahmad Fuadi's Novel Trilogy Negeri 5 Menara and Feasibility as Literature Teaching Material in High School - Alda Marsya Ayudia; Agus Nuryatin; Nas Haryati Setyaningsih (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study attempts to find and formulate the story structure pattern of the Negeri 5 Menara Trilogy, so that a storytelling technique is obtained that Ahmad Fuadi uses in creating a storyline. The data studied are in the form of acts and conflict events that build the story structure in the novel. The research data is then analyzed using the AJ Greimas narrative structure study with the heuristic semiotic reading technique to obtain a research idea scheme, and hermeneutics to obtain an interpretation of the meaning of events and storylines. The results of the analysis of the act scheme and functional model in the Negeri 5 Menara Trilogy produce a pattern of event development and storyline. The events or conflicts developed in the Negeri 5 Menara Trilogy always depart and center on the problems imposed or faced by the main character in achieving a goal. The subordinate characters occupy the functions of helping and opposing actants. The functional model that is determined as the storyline also shows the same pattern where the story always begins at the initial situation stage, then continues to the complete transformation stage and ends at the final situation stage. The Trilogy of Negeri 5 Menara has met the criteria for the suitability of teaching materials from the aspects of language, psychology, and cultural background. The analysis of the narrative structure of the Trilogy of Negeri 5 Menara is also in line with and can be adapted in literature learning in high school, especially in the text material of class XII novels in Phase F of the Merdeka Curriculum.